The Impact of Agile Leadership and Organizational Culture on Work-Life Balance (A Study at Regional Office I of the Badan Kepegawaian Negara) - Basuki, Vivilia (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
Research Aims:  The goal of this study is to explore the impact of agile leadership, organizational culture on work-life balance of employees at the Regional Office I of the Badan Kepegawaian Negara (BKN).Design/methodology/approach:  The study was carried out at the Regional Office I of the Badan Kepegawaian Negara (BKN) in Yogyakarta, involving 104 participants chosen using purposive sampling.  Data was collected through a Likert scale questionnaire and evaluated through the Partial Least Squares Structural Equation Modeling (PLS-SEM) method.Research Findings: The finding of this research highlight that both agile leadership and organizational culture significantly influence work-life balance.  Statistical analysis revealed that these two factors have a vital impact on improving the balance between work and personal life for employees.  Agile leadership contributes to greater flexibility in work management, enhancing job satisfaction and employee motivation.  Meanwhile, organizational culture, particularly a supportive and inclusive culture, has an even stronger impact on work-life balance.  This indicates that a combination of adaptive leadership and a culture that focuses on the well-being of employees is crucial for achieving optimal performance in organizations.Theoretical Contribution/Originality: This research offers a valuable theoretical contribution by integrating the concepts of agile leadership and organizational culture in the context of work-life balance in public sector organizations, specifically in BKN.  It fills a gap in existing literature by demonstrating how these two variables can work together to enhance employee well-being.  Furthermore, the study broadens the understanding of how a supportive organizational culture, focusing on flexibility and balance, directly influences employee satisfaction and performance.  Therefore, this research provides a fresh perspective on how public organizations can manage work-life balance to improve productivity and long-term effectiveness